Pengaruh Tingkat Pengangguran Terhadap Angka Kemiskinan Di Kabupaten Sinjai - Putri, Ayudia Amalia; Ikbal, Muhammad; Syarigawir, Syarigawir (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The aim of this research is to find out how the poverty level in Sinjai Regency is influenced by the unemployment rate. One of the main factors that can influence the poverty level of an area is unemployment. This study looks at how unemployment and poverty rates have been linked in recent years with secondary data from the Sinjai Regency Central Statistics Agency (BPS) and other reliable sources. Based on the research results, there is a positive and significant relationship between the poverty level and the unemployment rate in Sinjai Regency. The poverty rate increases along with the increase in the unemployment rate. Education, skills, and infrastructure are just some of the factors discussed in this analysis that may have an impact on poverty levels. It is hoped that this research can help local governments and other stakeholders develop more efficient strategies to reduce poverty and unemployment in Sinjai Regency. [Penelitian ini bertujuan untuk mengetahui bagaimana tingkat kemiskinan di Kabupaten Sinjai dipengaruhi oleh tingkat pengangguran. Salah satu faktor utama yang dapat mempengaruhi tingkat kemiskinan suatu daerah adalah pengangguran. Kajian ini melihat bagaimana tingkat pengangguran dan kemiskinan dikaitkan dalam beberapa tahun terakhir dengan data sekunder dari Badan Pusat Statistik (BPS) Kabupaten Sinjai dan sumber terpercaya lainnya. Berdasarkan hasil penelitian, terdapat hubungan yang positif dan signifikan antara tingkat kemiskinan dengan tingkat pengangguran di Kabupaten Sinjai. Angka kemiskinan meningkat seiring dengan meningkatnya angka pengangguran. Pendidikan, keterampilan, dan infrastruktur hanyalah beberapa faktor yang dibahas dalam analisis ini yang mungkin berdampak pada tingkat kemiskinan. Penelitian ini diharapkan dapat membantu pemerintah daerah dan pemangku kepentingan lainnya mengembangkan strategi yang lebih efisien untuk mengurangi kemiskinan dan pengangguran di Kabupaten Sinjai].